Market Power, Multimarket Contact and Pricing: Some Evidence from the US Automobile Market - Nina Leheyda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Multimarket contact is perceived to be one of those factors, which can facilitate and sustain implicit collusive (cooperative) arrangements. This paper attempts to develop new approaches to study the interdependence of firm behaviour across markets, especially in the context of differentiated products industries. I analyse the principle of conducting a test of the mutual forbearance hypothesis, and its application using particular data. The multimarket contact effects are studied within a structural oligopoly model for differentiated products for the US automobile market on the basis of the aggregate product-level data for 2001-2003. Some support has been found that multimarket contact may influence competition in the automobile market and increase the firms' strategic interdependence. This effect is, however, difficult to disentangle from the effect of the market concentration in the US automobile market (dominance of the market by the American Big Three) on the firm behaviour, which could also facilitate collusion. In other words, it is difficult to argue whether coordination is due to market concentration, or due to multimarket contact, or both. Concentration is argued to foster the slack, which is transferred through the multimarket contact.
Keywords: L25; L13; L62; 330; multimarket contact; collusion; automobile industry; test for non-nested hypothesis; menu test; structural oligopoly models; Kraftfahrzeugmarkt; Oligopol; Wettbewerbsbeschränkung; Schätzung; USA